Information technology strategies how leading firms use IT to gain an advantage - Rapp, William V. (Oxford University Press, 2011)
The focus of this text is to educate the reader on the strategic principles fundamental to using information technology to gain market control. It provides case examples of how to use IT to enhance existing core competencies and strategies.